IDENTIFIKASI JENIS, KERAPATAN DAN DIVERSITAS PLANKTON BENTOS SEBAGAI BIOINDIKATOR PERAIRAN SUNGAI PEPE SURAKARTA (IDENTIFICATION, DENSITY AND DIVERSITY OF PLANKTON AND BENTOS AS BIOINDICATOR AT PEPE RIVER SURAKARTA) - INDROWATI, METI; PURWOKO, TJAHJADI; RETNANINGTYAS, ESTU; YULIANTI, RARAS IKA; NURJANAH, SITI; PURNOMO, DWITO; WIBOWO, PANDU HARYO (Bioedukasi: Jurnal Pendidikan Biologi, 2012)
Plankton and benthos are two communities of organisms that can be used as bioindicator of aquatic environment. The purpose of this research were to determine kinds, density and diversity of plankton and benthos in Pepe river Surakarta as bioindicator.Study site was devided into 3 station as sampling location. Data sampling of identifying the type, density and calculating the value of diversity index (ID) according to Shannon Wiener for-mula. Investigations carried out measurements of environmental parameters, namely tempera-ture, pH and Dissolved OxygenThe result showed that 1) identified 20 kinds of plankton in Pepe river Surakarta namely Spirogy- ra, Eustbidentat, Pleurosigma, Oscilatoria, Euglena, Aungilospora, Gonatozygon, Dendrospora, Amoeba, Blepharisma sp, Hapalosiphon, Skeletonema, Synura, Stentor, Worochinia, Leptomitus, Peridinium, Paramecium, Volvox, Rhizosolenia, and Lyngbia with the composition and density vary between each sampling site, 2) Identified 3 kinds of benthos in Pepe river Surakarta namely Melanoides sp, Lymnaea sp and Fimbria fimbriata with the composition and density vary between each sampling site and 3 ) the Shannon Wiener Diversity Index (ID) of plankton and benthos in Pepe river Surakarta ranged from 0.98 to 1.98, showing the condition of polluted waters from mild to severe, varied between sampling sites.